High Precision Manufacturing Technology of Complex Lightweight Integral Panel of Spacecraft. Issue 1 (1st June 2022) - Liu, Shufen; Zhang, Bin; Zhang, Hengyi; Yi, Zhuoxun; Lai, Xiaoming; Yang, Kai
Abstract: For the problem that the traditional manufacturing method of spacecraft integral panel can not meet the manufacturing precision of the complex lightweight integral panel of the new generation of spacecraft, a method of roll bending in the state of flat plate first and then machining the grid features of the outer surface is proposed. ANSYS is used to simulate and analyze the internal stress when the integral panel with different roll bending radius when fitting with the tooling. It is obtained that it is easier to realize clamping and bonding by controlling the roll bending radius of the integral panel according to the negative difference. The clamping and positioning of the integral panel with vacuum adsorption device and the machining with variable helix angle milling cutter can effectively reduce the machining vibration. Combined with the processing compensation based on detection, the problem of out of tolerance of wall thickness in processing is solved, and finally the consistency of wall thickness is guaranteed. The experimental results show that this method can control the wall thickness of the integral panel within 1.05~1.33mm.